1994
DOI: 10.1210/endo.135.1.8013387
|View full text |Cite
|
Sign up to set email alerts
|

Negative cooperativity in the insulin-like growth factor-I receptor and a chimeric IGF-I/insulin receptor.

Abstract: Insulin and insulin-like growth factor-I (IGF-I) share a spectrum of metabolic and growth-promoting effects, mediated through homologous receptors that belong to the tyrosine kinase family. The dissociation rate of insulin from its receptor is affected by negative cooperativity, i.e. accelerates with increased receptor occupancy. The dose-response curve for the acceleration of tracer dissociation by unlabeled insulin has a distinct bell-shaped curve, with a progressive slowing down at insulin concentrations gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
65
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(72 citation statements)
references
References 0 publications
7
65
0
Order By: Relevance
“…Although the functional epitopes of the equivalent ligand binding site of both forms of the receptor are similar, certain amino acids appear to make ]insulin were performed with receptors isolated from detergent lysates of transfected cells. Data were analyzed by curve fitting to a two-site sequential model as described under "Experimental Procedures" (8,30). Results are mean Ϯ S.E.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the functional epitopes of the equivalent ligand binding site of both forms of the receptor are similar, certain amino acids appear to make ]insulin were performed with receptors isolated from detergent lysates of transfected cells. Data were analyzed by curve fitting to a two-site sequential model as described under "Experimental Procedures" (8,30). Results are mean Ϯ S.E.…”
Section: Resultsmentioning
confidence: 99%
“…Washing, blocking, receptor binding, and competitive binding assays with labeled and unlabeled peptides were performed as described. Binding data were analyzed by a two-site sequential model (8,30).…”
Section: Methodsmentioning
confidence: 99%
“…At very high insulin concentrations, more than one molecule can bind to the IR, and this results in a bell-shaped doseresponse curves for dissociation, whereas IGF-IR competition binding assays with IGF-I binding to the IGF-IR do not display this characteristic (53) (Fig. 3).…”
Section: Discussionmentioning
confidence: 99%
“…3). Christoffersen et al (53) concluded that IGF-I also has a bivalent binding mode and crosslinks two ␣-subunits at sites that are distinct from the IR binding sites. In this study, we show for the first time that the same is true for IGF-II binding to the IGF-IR, since we do not see a bell-shaped dose-response curves for dissociation.…”
Section: Discussionmentioning
confidence: 99%
“…Primers used for PCR were purchased from Genosys and all 5'-deoxynucleotide triphosphates were from Boehringer. Plasmids carrying cloned fulllength cDNAs encoding IR [19,20] and p85 [21 23] were generously provided by A. Ullrich and cloned full-length cDNA for IGF-1R [24,25] was obtained from P. De Meyts. The plasmids used for hybrid gene constructs were pBTMll6 ( [26]; carrying trpl) and pGAD GH ( [27]; carrying leu2), encoding the DNA binding domain of LEXA and GAL4 activation domain (GAD), respectively.…”
Section: Plasmid Constructionmentioning
confidence: 99%